性别决定区Y框蛋白9诱导人口腔鳞状细胞癌CAL27微管形成和上皮间质转化的机制初探 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2021)
OBJECTIVE: This study aimed to explore the effect of sex determining region Y-box 9 (SOX9) on the microtubule formation and epithelial-mesenchymal transition (EMT) of human oral squamous cell carcinoma (OSCC) CAL27 and the underlying mechanism. METHODS: SOX9-shRNA1 and SOX9-shRNA2 were designed and synthesized and then transfected into CAL27 cells. The expression of SOX9 was detected by quantitative real-time polymerase chain reaction. Microtubule formation assay was used to detect the change in the number of microtubule nodules after interfering with SOX9. Immunofluorescence was used to detect the Vimentin content. Western blot was used to detect the protein expression of EMT marker molecules and Wnt/β-catenin pathway-related proteins, such as E-cadherin, N-cadherin, Fibronectin, Wnt, β-catenin, T-cell factor-4 (TCF-4). RESULTS: The expression level of SOX9 significantly decreased after transfection with SOX9-shRNA1 and SOX9-shRNA2 in CAL27 cells (F=578.000, P=0.000; F=96.850, P=0.000). Interference with SOX9 inhibited the EMT of OSCC. After interference with SOX9, the number of tubules and Vimentin positive cells decreased significantly (F=169.700, P=0.000). The expression level of E-cadherin significantly increased (F=181.400, P=0.000). The expression levels of N-cadherin, Fibronectin, Wnt, β-catenin, and TCF-4 proteins significantly decreased (N-cadherin: F=101.400, P=0.000; Fibronectin: F=122.300, P=0.000; Wnt: F=70.290, P=0.000; β-catenin: F=81.740, P=0.000; TCF-4: F=37.020, P=0.000). CONCLUSION: Interference with SOX9 decreased Vimentin content and inhibited the microtubule formation and protein expression of EMT marker molecules, as well as the expression of proteins related to the Wnt/β-catenin pathway. Thus, SOX9 can induce microtubule formation and EMT in CAL27, which was related to the inhibition of the Wnt/β-catenin pathway activation.